Fire Trucks - Stille, Darlene R. (Minneapolis, MN Compass Point Books, 2002)
Old time fire engines - the ladder truck - the fire chief's car - fire tanker trucks - airport fire trucks - rescue trucks - clean-up trucks - fire department ambulance
K - 2
Keywords: Fire engines